Penggunaan Corong Berhitung Untuk Meningkatkan Kemampuan Operasi Hitung Penjumlahan Pada Murid Tunanetra Kelas Dasar II DI SLB Soppeng - Syamsuddin Syamsuddin; Triyanto Pristiwaluyo; Andi Budiman (Seminar Nasional LP2M UNM, 2019)
This study examines the low learning outcomes of blind students in mathematics, especially recognizing the arithmetic operations of students with visual impairments in SLB Soppeng. The formulation of the problem in this study is